Lehrerbild und Berufsperspektive von Lehramtsstudierenden im internationalen Ost-West-Vergleich. (Braunschweig - Sofia - Tallinn - Warschau) - Retter, Hein [Verfasser]; Bishkov, Georgi [Verfasser]; Saar, Aino [Verfasser]; Szymanski, Miroslaw S. [Verfasser] (My University, 1998)
Students of education were asked by questionnaire at the universities of Braunschweig (n=185), Sofia (n=199), Tallinn (n=165) and Warsaw ( n=119) firstly about their motives to become a teacher, secondly about the image of the teacher in society. The results make clear that the general motive for the intention to become a teacher in all groups of students asked is the affection towards children. The relatively low esteem of the teacher depends on unsufficient salary much more in post-socialism countries of Eastern Europe than in the Federal Republic of Germany, where other reasons are responsible that the teacher has not a top rank image in the view of students. (DIPF/orig.)
Keywords: P 3.2.3 Lehrer; G 2.4 Sozialer Wandel; I 2.2.2 Osteuropa; Lehramt; Lehrer; Berufsbild; Motivation; Berufsethos; Berufschance; Sozialprestige; Internationaler Vergleich; Osteuropa; Bulgarien; Estland; Polen